Mass spectrometry and its evolving role in assessing tissue specific steroid metabolism. (11th April 2016) - Andrew, Ruth; Homer, Natalie Z.M.
Abstract : Glucocorticoid hormones play vital roles in regulating diverse biological processes in health and disease. Tissue levels are regulated by enzymes which activate and inactivate hormones. The enzyme, 11β-hydroxysteroid dehydrogenase type 1 (11βHSD1), in particular, has been identified as a potential drug target; inhibiting this enzyme attenuates glucocorticoid action by lowering local levels of active hormone. A variety of mass spectrometric approaches have been developed to characterize this enzyme in vivo . Endogenous glucocorticoids and their metabolites can be profiled in urine by GC–MS and circulating steroids are now more commonly quantified by liquid chromatography tandem mass spectrometry. Tracer dilution studies have allowed rates of generation of glucocorticoids by the enzyme to be distinguished from hormone generated directly by the adrenal glands and, in combination with arterio-venous (AV) sampling, rates of production by specific tissues have been quantified. This has allowed the contribution of liver, adipose, muscle and brain to cortisol production in metabolic disease and hence prioritized drug targets. Most recently MS imaging in combination with on-tissue derivatization has been developed to profile oxo-steroids in tissue sections, allowing molecular maps to be generated across complex tissues, where regional functions are important. The review provides a synopsis of how measurement of steroids by MS has evolved with technological advances and this has provided insight into the dynamic turnover of glucocorticoids in vivo, highlighting the milestones that have advanced the field and identifying the remaining challenges for researchers, in terms of analytical chemistry and endocrine physiology and biochemistry.